IJTIHAD METHOD SHAYKH ATHIYAH SAQR ABOUT THE OBLIGATION OF THE HUSBAND TO FULFILL THE DESIRES OF THE WIFE WHEN CRAVINGS - Ainii, Nuur; Azwar, Zainal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Support in a marital relationship is an obligation for a husband towards his wife and children.Fulfilling the wife's wishes when she has cravings is categorized as a husband's maintenanceaccording to Sheikh Athiyah Saqr, which is also legally obligatory. However, seeing the phenomenonof excessive coveting from wives that often occurs nowadays, it is necessary to classify wives' desires,which the husband must fulfill by law. This research aims to analyze Sheikh Athiyah Saqr's method ofijtihad in his fatwa on the obligation for husbands to fulfill their wives' desires when they desire themand to relate the relevance to current phenomena. This research uses the library research method. Thedata collection technique used is library research. The data analysis technique used in this research isthe descriptive method. The result of this research is that Sheikh Athiyar Saqr in determining thisfatwa used the qiyas and maslahah murlah methods. According to Sheikh Athiyah Saqr, the obligationof a husband to fulfill his wife's wishes when she desires is translated into the obligation of thehusband to provide his wife with daily living. Apart from that, fulfilling the wife's wishes by thehusband is considered to bring benefits to the wife and the fetus. However, it is necessary to limit thewife's wishes which must be fulfilled by the husband, namely wishes that do not violate the Shari'a, donot bring harm, and are still within the limits of the husband's capabilities